Faith-Integrated Environmental Education in a Muslim-Majority Rural Community: A Qualitative Case Study South Sulawesi, Indonesia - Rudhi Rudhi; Herianti Herianti; Nurdin Nurdin; Nursyamsidar Nursyamsidar; Nurhaliza Nurhaliza; Nia Kartika Putri; Sita Damayantih; Indo Aco; Rahman Rahman; Naufal Fajrul Ihsan; Agung Setia Budi Wahid (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Education for Sustainable Development increasingly recognizes that durable environmental behavior is rooted in intrinsic motivation rather than information provision alone. In Muslim-majority communities, Islamic ecotheology offers a culturally authentic foundation for environmental education, yet empirical research on its operationalization in real community settings remains limited. This qualitative case study investigates how Islamic ecotheological values function as a framework for non-formal and informal environmental education in Ganra Village, South Sulawesi, Indonesia, examining the factors sustaining community-wide environmental learning. Data were collected through purposive semi-structured interviews, participatory observation, and document analysis, then analyzed using the Miles, Huberman, and Saldaña interactive model. Three principal findings emerged: first, environmental awareness is grounded in Islamic faith, framing environmental care as ibadah (worship) through khalifah (vicegerency) and mizan (balance); second, ecotheological values are operationalized through five structured educational channels, including communal rituals and the BERGEGAS waste management program; third, six interdependent factors sustain learning, notably strong leadership, village regulations, and a deep Islamic heritage. The Ganra Village case demonstrates that faith-integrated environmental education, when institutionally scaffolded, produces highly persistent pro-environmental outcomes. This ProKlim-awarded model offers a replicable template for faith-based environmental education globally, advancing scholarship by demonstrating how ecotheology functions as a pedagogically coherent framework.